(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The study has been designed to compare the outcome of percutaneous nephrolithotomy with (Group A) or without nephrostomy tube (Group B) for the management of renal stone disease. JJ stents were given to all cases of both groups. Comparison of outcome between groups shows that urinary leakage time was significantly longer in Group B than that in Group A (24.0 ± 6.2 vs 7.3 ± 3.9 hours; p<0.001). Visual analogue pain score was also significantly high in Group B than in Group A (4.7 ± 0.8 vs 2.4 ± 0.5; p<0.035). Patients in Group B stayed in hospital on an average 4 days, while the Group A patients stayed in hospital on an average 2.5 days (p<0.029). The mean hemoglobin decrease in 24 hours in Group B and in Group A (0.5 ± 0.4 and 0.5 ± 0.4 respectively) did not show any significant difference (p<0.895). In conclusion, percutaneous nephrolithotomy without nephrostomy tube can be practiced in the management of selective cases of renal stones diseases.